2015
DOI: 10.3923/rjes.2015.280.288
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Methane Gas Generation Rate from Sanandaj City Landfill Using LANDGEM Software

Abstract: The main gas arising from landfills is methane. The greenhouse effect of methane is 21 times more serious than that of carbon dioxide. On the other hand, this gas has a significant potential for producing energy, so that in cases of application of a suitable technology, a considerable energy from this gas could be extracted and used. One of the mathematical models used for estimation of the amount of methane potential in landfills is LANDGEM software, which was applied in the present research study. This was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…The CH 4 generated or emitted from landfill can be used as a source of energy (Faour et al, 2007; Karanjekar et al, 2015; Kormi et al, 2017; Salami et al, 2020; Shin et al, 2005) but unfortunate most developing countries especially in Africa are tapping these benefits of waste to wealth and waste to energy principles. The amount of CH 4 emission from Sanandaj landfill has been estimated at 410, 549, and 671 m 3 /hr for 2023, 2028, and 2033 respectively (Shahmoradi et al, 2015). In another study, it was shown that 1.164 × 106 m 3 /annum of CH 4 was produced in Kachok dumpsite (Kenya) in the year 2018 (Kabok et al, 2021).…”
Section: Previous Work On Assessment Of Air Pollutantsmentioning
confidence: 99%
“…The CH 4 generated or emitted from landfill can be used as a source of energy (Faour et al, 2007; Karanjekar et al, 2015; Kormi et al, 2017; Salami et al, 2020; Shin et al, 2005) but unfortunate most developing countries especially in Africa are tapping these benefits of waste to wealth and waste to energy principles. The amount of CH 4 emission from Sanandaj landfill has been estimated at 410, 549, and 671 m 3 /hr for 2023, 2028, and 2033 respectively (Shahmoradi et al, 2015). In another study, it was shown that 1.164 × 106 m 3 /annum of CH 4 was produced in Kachok dumpsite (Kenya) in the year 2018 (Kabok et al, 2021).…”
Section: Previous Work On Assessment Of Air Pollutantsmentioning
confidence: 99%
“…These approaches include first-order decay (FOD), LFG generation models, including the US EPA's LFG emissions model (LandGEM), e-pollutants release and transfer registers (E-PRTR) (Fr) model, Intergovernmental Panel on Climate Change (IPCC) model, and Afvalzorg model [3]. One of the most commonly used and most flexible models is LandGEM [4]. This model that has been developed by the United States Environmental Protection Agency (USEPA), estimates an acceptable quantity of produced methane in landfills over time.…”
Section: Introductionmentioning
confidence: 99%
“…It estimates the volume and composition of the generated methane throughout time because of the degradation of organic matter in the landfill. In addition, this model is an important step in developing a landfill project, which allows to estimate the available recoverable quantity of methane as fuel energy over time [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation